The evolution of jurisprudence of the International Court of Justice in cases of maritime delimitation - Połatyńska, Joanna (Acta Universitatis Lodziensis. Folia Iuridica, 2012)
Since territorial boundaries are considered to remain untouched, the delimitation of maritime boundaries is the main battlefield of territorial disputes amongst States. It is estimated that until today only less than half potentially necessary boundaries has been determined. Undoubtedly, the States should reach the agreement in order to determine boundaries between their maritime zones. Only in cases when Parties are unable to reach it, the delimitation should be transferred to International Court or Tribunal. The judgments in cases concerning maritime delimitation are the sixth part of all the ICJ’s judgments. Within sixty years of the jurisprudence of the ICJ, these judgments have become the unique case law.